Vestibulotoxicity and balance problems associated with cisplatin chemotherapy in adult cancer survivors - Prayuenyong, Pattarawadee (2021)
Introduction and aims Cisplatin is an effective chemotherapeutic agent, but it has common side effects of ototoxicity and peripheral neuropathy which could potentially lead to balance problems. While cisplatin cochleotoxicity (causing hearing loss or tinnitus) is well documented, vestibulotoxicity (causing balance problems) is still unclear in literature. This thesis aimed to examine vestibular dysfunction and balance problems associated with cisplatin chemotherapy in adult cancer survivors to determine the epidemiology and impact of the problems. The project consists of 4 original research studies to evaluate the problems from patients and healthcare professional perspectives. Specific objectives of the studies were I. To examine current evidence and identify research gaps on vestibulotoxicity associated with cisplatin chemotherapy II. To explore knowledge, experiences, and opinions of audiovestibular professionals about cisplatin vestibulotoxicity III. To assess the vestibular function and balance problems in adult cancer survivors who had completed cisplatin chemotherapy treatment IV. To explore the lived experience and attitudes towards balance problems in adult cancer survivors who had completed cisplatin chemotherapy treatment